COMPARATIVE HISTOLOGICAL CHANGES IN BONE AND LIVER IN RESPONSE TO EXTRACT OF TRIFOLIUM REPENS AND EQUISETUM ARVENSE IN ADULT FEMALE WISTAR RATS - SUKRITHA KM; VISHALI N; KAVITHA B; BHAVYA J MENON (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study is to evaluate the histological changes in bone tissue and assess potential adverse effects on liver tissue in an estrogen-deficient rat model (ovariectomized rats) treated with Trifolium repens (white clover) and Equisetum arvense (horsetail) extracts. Methods: A total of 56 female Albino Wistar rats (7–9 weeks old, 200–220 g) were obtained from Cape Bio Laboratory and Research Centre. Animals were acclimatized under standard laboratory conditions in animal housing (temperature: 22±3°C; humidity: 50–55%; 12-h light/dark cycle). Bilateral Ovariectomy was performed to induce estrogen deficiency. One month post-surgery, Ovariectomized (OVX) rats were orally administered 60 mg/day of T. repens and E. arvense extract for 45–90 days. At the end of the treatment period, femur and liver tissues were collected for histological examination. Results: Ovariectomy resulted in a significant increase in body weight and an increased number of osteoclasts, along with noticeable histological changes in the femur compared to the control group. Treatment with E. arvense and T. repens did not cause any adverse histological changes in the liver. Among the two treatments, E. arvense was more effective in mitigating bone loss induced by estrogen deficiency. Conclusion: These findings suggest that E. arvense appears to be more effective than T. repens in preserving bone integrity in ovariectomized rats, likely by reducing bone turnover through the inhibition of bone resorption. In addition, both herbal extracts were found to be safe for liver tissue at the administered dose.